2020
DOI: 10.1002/adfm.202004514
|View full text |Cite
|
Sign up to set email alerts
|

Robust Polyethylenimine Electrolyte for High Performance and Thermally Stable Atomic Switch Memristors

Abstract: Organic polymer solid electrolytes show interesting application prospects in resistive switching memories and brain-inspired computing ionic devices. However, polymer electrolytes can easily decompose under heat treatment and their ionic conductivity can vary significantly at different temperatures. Among the reported polymer memristors, most of them lack sufficient reproducibility, endurance, stability, uniformity, and inter alia heat tolerance. Based on a molecular group that is thermally stable over a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 57 publications
0
35
0
Order By: Relevance
“…Moreover, there are many challenges in achieving synaptic memristors based on organic 2D materials. Several RS mechanisms have been proposed to address the observed RS behaviors in organic 2D materials, such as metal CFs, 106 charge transfer, 107 charge trapping and detrapping, 105 conformation change, 108 and redox reaction. 109 This subsection mainly introduces the investigation progress of 2D organic materials and their composites in RS devices.…”
Section: Memristors Based On Vdwhsmentioning
confidence: 99%
“…Moreover, there are many challenges in achieving synaptic memristors based on organic 2D materials. Several RS mechanisms have been proposed to address the observed RS behaviors in organic 2D materials, such as metal CFs, 106 charge transfer, 107 charge trapping and detrapping, 105 conformation change, 108 and redox reaction. 109 This subsection mainly introduces the investigation progress of 2D organic materials and their composites in RS devices.…”
Section: Memristors Based On Vdwhsmentioning
confidence: 99%
“…The work demonstrates that crystalline inorganic-organic hybrid POMs are promising materials for making memristors with superior performance.Memristors are leading candidates for the next generation non-volatile memory devices owing to their low power consumption, high access speed, multi-state switching and device scalability. [1][2][3][4][5][6][7] The development of memristors with high performance and reliability under special/harsh environments is in great demand so that they can be applied in many promising fields, such as aerospace, geothermal, oil and gas industries. [8] In the past few decades, great efforts have been paid to improve the switching performance of memristors at high temperatures because the working mechanisms of memory devices, including filamentary conduction, space charge trapping, valence and conformation changes and…”
mentioning
confidence: 99%
“…Organic materials often show better flexibility than inorganic materials, which are potential candidates for fabricating flexible memristive devices and arrays. Common organic materials, such as albumin (Chen et al, 2015), collagen (Zeng et al, 2019), silk fibroin (Kook et al, 2020;Wang et al, 2016a), polyethyleneimine (PEI) (Yang et al, 2020) and poly(1,3,5-trivinyl-1,3,5trimethylcyclotrisiloxane) (pV 3 D 3 ) (Jang et al, 2019;Jang J. et al, 2018a), have demonstrated their promising application in flexible memristive devices and arrays. By employing waferscale ultraviolet photolithography technology, a silk fibroin-based memristive array was successfully fabricated on a parylene-C film with robust flexibility (Kook et al, 2020).…”
Section: Flexible Organic Memristive Arraysmentioning
confidence: 99%